ELECTRONICALLY MEDIATED SIMULATION AS A STRATEGY FOR SKILLS DEVELOPMENT IN THE AREA OF COMPUTER MAINTENANCE - Redondo Robles , Carlos Alberto
The purpose of the research was to use electronically mediated simulation as a strategy for developing Computer Maintenance skills, in technical training contexts. The research is qualitative, descriptive and field approach, with a non-experimental design of a cross-sectional or transectional type. The results indicate that, through interaction with the simulated environment, interest in the object of study is generated, investigating, experimenting and generating new ways of learning; At its core, learners come to discover for themselves how the system works, in an active and constructive way. In conclusion, through implementation of electronically mediated simulation, not only they can develop specific or technical competencies, but 21st century competencies, essential both in the improvement of the maintenance action, and in their labor and social performance in the productive sector.